Connecting to the Khans: Shaping National Identity through Education in Kazakhstan and the Beliefs of the Next Generation - Matthew Stein (Arizona State University, 2011)
When the Soviet Union collapsed in 1991, Kazakhs did not make up the majority of the population in their own titular state. Since then, Kazakhs have become the majority ethnic group and the government has revised their education system to reflect this demographic change. Education is an important tool for shaping national identity in a multiethnic state, especially one undergoing demographic shifts. This article will look at the demographic change in Kazakhstan, how it has affected education and in turn how this has shaped national identity on young generations. This transformation of national identity is important to monitor and understand as Kazakhstan continues to develop and become an important security partner and increasingly vital source of energy supplies for Asia and Europe.